Shore type effect on onshore wave energy converter performance - Yamac, Halil Ibrahim; Koca, Ahmet (Pergamon-Elsevier Science Ltd, 2019)
Oscillating Water Column (OWC) is one of the WEC devices, which converts wave energy to electrical power. In this study, analysis of OWC is made in Numerical Wave Tank. Finite Volume Method based on Reynolds-Averaged Navier-Stokes equations is used. Turbulence model as k-epsilon, Volume of Fluid Method and Dynamic Mesh Technique are chosen options to have transient simulation in Fluent software. The numerical wave tanks are modelled at the length of 400m for 9s wave period and length of 211m for 6s wave period to obtain the desired wave properties because of the wave generation method used. The wave lengths are 55.8m for 6s wave period and 111.4 for 9s wave period. The initial water depth is 24.5m for all cases. The obtained results are volume fraction, velocity, vorticity and turbulence kinetic energy contours. Pressure and velocity data are used for computation and comparison of power output of cases. Power output results vary from 34.5 to 45.0 Watt for 1m wave height, 121.5 to 240.8 Watt for 2m wave height and 425.3 to 1227.6 Watt for 4m wave height. The best performances are obtained from convex arc structure at 4m wave height at 6s and 9s wave periods.
Keywords: Wave energy; Shore type effect; Onshore oscillating water column; Computational fluid dynamics